Spontaneous Formation of Altermagnetism from Orbital Ordering - Leeb, Valentin; Mook, Alexander; Šmejkal, Libor; Knolle, Johannes (Physical review letters, 2024)
Altermagnetism has emerged as a third type of collinear magnetism. In contrast to standard ferromagnets and antiferromagnets, altermagnets exhibit extra even-parity wave spin order parameters resulting in a spin splitting of electronic bands in momentum space. In real space, sublattices of opposite spin polarization are anisotropic and related by rotational symmetry. In the hitherto identified altermagnetic candidate materials, the anisotropies arise from the local crystallographic symmetry. Here, we show that altermagnetism can also form as an interaction-induced electronic instability in a lattice without the crystallographic sublattice anisotropy. We provide a microscopic example of a two-orbital model showing that the coexistence of staggered antiferromagnetic and orbital order can realize robust altermagnetism. We quantify the spin-splitter conductivity as a key experimental observable and discuss material candidates for the interaction-induced realization of altermagnetism.